Review of Phytochemistry and Hypolipidemic Effects of Vaccinium oxycoccus: Review Article (Journal of Pharma Insights and Research, 2024)
Cranberry (Vaccinium oxycoccus), a small evergreen shrub of the Ericaceae family, represents a valuable medicinal plant with diverse therapeutic applications in both traditional and modern medicine. The fruit's remarkable properties stem from its rich composition of bioactive compounds, primarily flavonoids including anthocyanidins, proanthocyanidins, and phenolic acids, which contribute to its potent antioxidant activity. Beyond its basic nutritional value of minerals and vitamins, cranberry demonstrates a uniquely low sugar content compared to other berries. Clinical and preclinical studies have established its efficacy in preventing urinary tract infections, exhibiting anticancer properties, and protecting cardiovascular health. The fruit shows promising results in obesity management and metabolic disorder treatment, with significant effects on lipid metabolism and atherosclerosis prevention attributed to its polyphenolic content. Research has documented its ability to regulate blood pressure, modulate glucose metabolism, and protect mitochondrial function. The antimicrobial properties extend beyond urinary tract applications, while anti-inflammatory effects suggest broader therapeutic potential. Modern investigations continue to uncover novel applications in functional foods and preventive medicine, particularly focusing on metabolic disorders and cardiovascular health. These findings establish cranberry as a significant natural therapeutic agent, warranting further investigation into its molecular mechanisms and clinical applications